Rethinking Unhealthy Alcohol Use in the United States: A Structured Review - Joseph R Volpicelli; Percy Menzies (SAGE Publishing, 2022)
Greater than moderate alcohol use spans a continuum that includes high levels of total alcohol consumed per period (heavy drinking) as well as episodes of intense drinking (binges) and can give rise to alcohol use disorder (AUD) when associated with an inability to control alcohol use despite negative consequences. Although moderate drinking and AUD have standard, operable definitions in the United States (US), a significant "gray area" remains in which an individual may exceed recommended drinking guidelines but does not meet the criteria for AUD (hereafter referred to as unhealthy alcohol use). To address this need, we conducted a structured literature search to evaluate how this gray area is defined and assess its burden within the US. For purposes of this review, we will refer to this gray area as "unhealthy alcohol use." Although numerous terms are used to describe various unsafe drinking practices, our review did not find any studies in which the specific prevalence and/or burden of unhealthy alcohol use was evaluated. That is, we found no studies that focus exclusively on individuals who exceed moderate drinking guidelines but do not meet AUD criteria. Furthermore, we did not discover an established framework for identifying individuals with unhealthy alcohol use. The lack of a consistent framework for identifying unhealthy alcohol users has significant implications for patient management and disease burden assessment. Therefore, we propose the following framework in which unhealthy alcohol use comprises 2 distinct subpopulations: those at risk of experiencing alcohol-related consequences and those who have subthreshold problems associated with use. The former, termed "risky drinkers," are defined by exceeding recommended guidelines for moderate drinking (⩽1 or 2 drinks per day for women and men, respectively). People with subthreshold problems associated with use, defined as exhibiting exactly 1 AUD symptom, would be classified as "problematic drinkers" within this proposed framework. These definitions would help bring the core elements of unhealthy alcohol use into focus, which in turn would help identify and provide management strategies sooner to those affected and reduce the overall burden of unhealthy alcohol use.